The relationship of dietary patterns and lifestyle on cardiovascular disease risk factors among college students. - Palis, E. A. G.; Hurtada, W. A.; Mera F. F.; Talavera, M. T. M. (2003)
This study focused on the determination of the relationship of dietary patterns and lifestyle on the cardiovascular disease risk factors among college students of the University of the Philippines Los Baños, Philippines. Three dietary patterns with different characteristics were identified. No significant relationships were observed among all dietary patterns with conventional cardiovascular risk factors. Consumption of less than 1 standard drink and 1 to 4 standard drinks of alcohol per week and moderate level of physical activity had a negative significant relationship with at least 2 cardiovascular disease risk factors.
Keywords: Cardiovascular diseases; Lifestyles; Diet